BRAND IMAGE AND PROMOTION ON PRODUCT PURCHASE DECISIONS: A SAGA OF GENERATION Z IN BANDAR LAMPUNG CITY - Musyrifah Maliki, Raudoh; Syamsul Hilal; Hanif, Hanif (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Changes in Generation Z's preferences and purchasing behavior, especially in an increasingly competitive digital environment, are a challenge for e-commerce companies in building a strong brand image and implementing effective promotional strategies. This study aims to identify the influence of brand image and promotion on e-commerce product purchasing decisions among Generation Z in Bandar Lampung City. A quantitative approach was used in this study, with primary data collected through questionnaires and secondary data as supporting data. The research population was Generation Z in Bandar Lampung City, with a sample size of 100 people determined using the Slovin formula. Data analysis was carried out using SPSS software. The results showed that brand image and promotion significantly influenced purchasing decisions. Brand image, which consists of the image of the maker, the image of the user, and the image of the product, has been proven to be able to build consumer trust, loyalty, and positive perceptions of the brand. On the other hand, promotions designed with strategically relevant message, media, time, and frequency elements have succeeded in attracting interest and driving purchasing decisions. This study provides theoretical and practical contributions in understanding the behavior of Generation Z in the context of e-commerce, as well as being a reference for companies to optimize marketing strategies that focus on brand image and targeted promotions.